Strain-Induced Surface Interface Dual Polarization Constructs PML-Cu/Bi12O17Br2 High-Density Active Sites for CO2 Photoreduction - Zhang, Yi; Guo, Fangyu; Di, Jun; Wang, Keke; Li, Molly Meng‑Jung; Dai, Jiayu; She, Yuanbin; Xia, Jiexiang; Li, Huaming (Nano-Micro Letters, 2024)
The insufficient active sites and slow interfacial charge transfer of photocatalysts restrict the efficiency of CO2 photoreduction. The synchronized modulation of the above key issues is demanding and challenging. Herein, strain-induced strategy is developed to construct the Bi–O-bonded interface in Cu porphyrin-based monoatomic layer (PML-Cu) and Bi12O17Br2 (BOB), which triggers the surface interface dual polarization of PML-Cu/BOB (PBOB). In this multi-step polarization, the built-in electric field formed between the interfaces induces the electron transfer from conduction band (CB) of BOB to CB of PML-Cu and suppresses its reverse migration. Moreover, the surface polarization of PML-Cu further promotes the electron converge in Cu atoms. The introduction of PML-Cu endows a high density of dispersed Cu active sites on the surface of PBOB, significantly promoting the adsorption and activation of CO2 and CO desorption. The conversion rate of CO2 photoreduction to CO for PBOB can reach 584.3 μmol g−1, which is 7.83 times higher than BOB and 20.01 times than PML-Cu. This work offers valuable insights into multi-step polarization regulation and active site design for catalysts. Highlights: 1 Strain induces coupling in Bi12O17Br2 and Cu porphyrin-based monoatomic layer (PML-Cu), constructing Bi–O bonding interface in PML-Cu/BOB (PBOB). 2 Surface interface dual polarization boosts internal electric field, promoting electron transfer. 3 PML-Cu provides high density of dispersed active Cu sites in PBOB, enhancing CO2 photoreduction.